2003
DOI: 10.1176/appi.ajp.160.10.1892
|View full text |Cite
|
Sign up to set email alerts
|

Resting Regional Cerebral Blood Flow and Gambling Task Performance in Cocaine-Dependent Subjects and Healthy Comparison Subjects

Abstract: Resting anterior cingulate and dorsolateral prefrontal cortex rCBF is significantly related to decision making, as assessed by the Gambling Task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 8 publications
6
55
2
1
Order By: Relevance
“…Tucker et al 102 also found a significant correlation between Gambling Task performance and anterior cingulate regional cerebral blood flow (rCBF) changes in cocainedependent subjects. Interestingly, however, the relationship was in the opposite direction as that reported by Adinoff et al, 100 i.e., increased anterior cingulate rCBF was correlated with poorer Gambling Task performance. Differences between these two studies may be explained by the testing of recently using cocaine-addicted subjects (last use 4.6 ± 3.1 days prior to testing) in the Adinoff et al study 100 vs. at least two weeks abstinence in the Tucker et al study.…”
Section: Decision Makingcontrasting
confidence: 52%
See 3 more Smart Citations
“…Tucker et al 102 also found a significant correlation between Gambling Task performance and anterior cingulate regional cerebral blood flow (rCBF) changes in cocainedependent subjects. Interestingly, however, the relationship was in the opposite direction as that reported by Adinoff et al, 100 i.e., increased anterior cingulate rCBF was correlated with poorer Gambling Task performance. Differences between these two studies may be explained by the testing of recently using cocaine-addicted subjects (last use 4.6 ± 3.1 days prior to testing) in the Adinoff et al study 100 vs. at least two weeks abstinence in the Tucker et al study.…”
Section: Decision Makingcontrasting
confidence: 52%
“…Interestingly, however, the relationship was in the opposite direction as that reported by Adinoff et al, 100 i.e., increased anterior cingulate rCBF was correlated with poorer Gambling Task performance. Differences between these two studies may be explained by the testing of recently using cocaine-addicted subjects (last use 4.6 ± 3.1 days prior to testing) in the Adinoff et al study 100 vs. at least two weeks abstinence in the Tucker et al study. 102 Using fMRI, Paulus et al 120 demonstrated a relationship between anterior cingulate and DLPFC (among other regions) activity and outcome predictability during a two-choice decision task.…”
Section: Decision Makingcontrasting
confidence: 52%
See 2 more Smart Citations
“…[12][13][14] Certain antihypertensive agents and cocaine have also been shown to decrease resting cerebral perfusion, though recent studies have demonstrated preservation of CBF during short-and long-term treatment of moderate hypertension. 15,16 Brain Death. ASL is sensitive in demonstrating states of hypoperfusion.…”
mentioning
confidence: 99%